Historical consciousness and identity formation: mutual dependency - Chaves de Rezende Martins, Estevao (Revista Territórios e Fronteiras, 2022)
Abstract : How does historical consciousness come about? Recognizing the past depends on a factorial network. In the center of this network is the acting person, himself a historically and socio-psychologically educated being. Such a network is formed from factors that interweave acting people, their personal history and their (immediate) cultural environment culturally and socially. The meaning of history, the meaning of the formed subject identity and the historical awareness acquired in stages are closely related. Keywords: Historical consciousness; Historical education; Historical knowledge; Historical culture. Resumo: Como surge a consciência histórica? Reconhecer o passado depende de uma rede fatorial. No centro dessa rede está a pessoa atuante, ela mesma um ser educado histórica e sócio-psicologicamente. Tal rede é formada a partir de fatores que entrelaçam cultural e socialmente as pessoas atuantes, sua história pessoal e seu ambiente cultural (imediato). O sentido da história, o sentido da identidade do sujeito formado e a consciência histórica adquirida em etapas estão intimamente relacionados. Palavras-chave: Consciência histórica; Educação histórica; Conhecimento histórico; Cultura histórica.